Phlebographic Detection Of Deep Vein Thrombosis After Major Surgery - Kesarwani, Dr. R.C.; Katiyar, Dr. R.K.; Mittal, Dr. Shashank (Indian Journal of Plastic Surgery, 1992)
60 patients from Various surgical disciplines, one third of which already with pre-existing venous diseases were subjected to phlebography for detection of deep vein thrombosis. Results are presented.
Keywords: Early detection; Thrombosis